2018
DOI: 10.1590/1413-70542018426019018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in natural populations of Hancornia speciosa Gomes: Implications for conservation of genetic resources

Abstract: The continuing fragmentation of forests has been a threat to the maintenance of genetic resources. Genetic diversity is fundamental to the survival of species in natural environments in the long term, as well as being the basis for genetic improvement. The objective of this study was to evaluate the genetic diversity in natural populations of Hancornia speciosa and to contribute to the development of conservation strategies. We sampled 105 individuals of H. speciosa, distributed in seven populations. The ISSR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…They concluded there were allometric differences due to phylogenetic evaluations, which are not influenced by the environment. Ganga et al (2010) found for H. speciosa trees an average of 4.58 m for height, ranging from 1.5 m to 10 m. The observed variation may be related to the existing phenotypic variation among trees, also observed for the CBH and DBH, and genetic diversity (FAJARDO et al, 2018). The relation between DBH and total height is a key factor to help trees to maintain their balance and is related to the ability of the trunk to remain standing.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…They concluded there were allometric differences due to phylogenetic evaluations, which are not influenced by the environment. Ganga et al (2010) found for H. speciosa trees an average of 4.58 m for height, ranging from 1.5 m to 10 m. The observed variation may be related to the existing phenotypic variation among trees, also observed for the CBH and DBH, and genetic diversity (FAJARDO et al, 2018). The relation between DBH and total height is a key factor to help trees to maintain their balance and is related to the ability of the trunk to remain standing.…”
Section: Discussionmentioning
confidence: 89%
“…All trees were inventoried in natural remnants of seasonal semideciduous Atlantic Forest in Rio Grande do Norte State, Brazil. The H. speciosa populations are historically threatened by the marked reduction of the natural habitats due to the deforestation and development of monoculture agricultural activities, causing a decrease in the effective population size (FAJARDO et al, 2018). The geographical coordinates of each plant were recorded by the Global Positioning System (GPS) in two populations in an area called Macaíba.…”
Section: Spatial Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…The conservation of genetic resource should be carried out using the knowledge of the diversity and genetic structure of its populations. Genetic diversity can also be used to select more divergent individuals according to the research study objective (Nunes et al 2021) and is also the basis for genetic improvement (Fajardo et al 2018). However, some species have particularities concerning the physiologic aspect, reproductive system, etc., which also is very important and demand specific strategies to conserve their genetic resources.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…The species has high commercial interest due to its fruits (Nunes et al 2022b) used for the production of pulp and ice cream, produced during two annual harvest seasons. H. speciosa is a species threatened by habitat loss (Fajardo et al 2018;Álvares-Carvalho et al 2022;Silva et al 2022) and is considered a priority for research in Brazil (Coradin et al 2018). Moreover, its recalcitrant seeds have shown an increase in longevity under storage in an osmoprotective solution (Nunes et al 2022a).…”
Section: Introductionmentioning
confidence: 99%